2009
DOI: 10.1530/rep-08-0491
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming: prenatal androgen excess disrupts ovarian steroid receptor balance

Abstract: Steroid hormones play an important role in reproduction and the receptors through which they signal change in a developmental time, follicle stage, and cell-specific manner. Disruption in steroid receptor expression affects follicle formation and differentiation. In this study, using prenatal testosterone (T) and dihydrotestosterone (DHT)-treated female sheep as model systems we tested the hypothesis that prenatal androgen excess disrupts the developmental ontogeny of ovarian steroid receptor protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 79 publications
(128 reference statements)
2
134
0
1
Order By: Relevance
“…These results are consistent with those of a previous study by Ortega et al, which reported enhanced protein expression of AR in the foetal ovary of Suffolk sheep, in that case detected by optical density (Ortega et al 2009). The inability to detect differences in AR mRNA levels between PA and control ovaries is consistent with the findings of Hogg et al (2011) in Scottish Greyface sheep.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with those of a previous study by Ortega et al, which reported enhanced protein expression of AR in the foetal ovary of Suffolk sheep, in that case detected by optical density (Ortega et al 2009). The inability to detect differences in AR mRNA levels between PA and control ovaries is consistent with the findings of Hogg et al (2011) in Scottish Greyface sheep.…”
Section: Discussionsupporting
confidence: 94%
“…The major strength of the well-validated imaging approach used in this study is the visualization of in situ localization of proteins within cells of interest. Quantification of biological markers using this approach has been successfully applied to quantify immunoreactivity in different tissues (Lejeune et al2008, Ortega et al 2009a). This type of densitometrical methodology has been previously validated by biochemical methods of protein induction and quantification (Peretti-Renucci et al 1991).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism by which hyperandrogenemia could be linked to increased miscarriage risk is not known. The specific cytokine profile of PCOS patients is likely to be related to the lower implantation rate, since follicular fluid appears to function as an embryotrophic agent (35,36). Certain studies have revealed higher levels of testosterone in the follicular fluid of patients with PCOS (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperandrogenism in PCOS may proceed via dysregulated paracrine/endocrine control of androgen synthesis (37), or result from adrenal androgen excess (39,40). Intraovarian androgens have been found to promote GC proliferation and inhibit GC apoptosis in PCOS patients, particularly in small follicles whose GCs are rich in androgen receptors (35,36), indicating that androgens may have a crucial effect on GC development, and intraovarian androgen may play an important role in the pathogenesis of PCOS via regulating early follicle growth. In this study, we observed that excess androgen decreased the expression of the examined HOXA10 genes in GCs, which suggests that androgenic regulation of these genes may specifically contribute to folliculogenesis.…”
Section: Discussionmentioning
confidence: 99%